Adnotacja w rosyjskim "Liber Copulatorum" (1868-1882) jako rodzaj tekstu w świetle analizy tekstologiczno-kodykologicznej - Owsiński, Piotr Aleksander (Acta Neophilologica, 2022)
This paper, involving a textlinguistic-codicological analysis, attempts to identify specific features of the Russian administrative language in the entries of the parish register from Busko-Zdrój in the 19th century. The aim of the investigation is to answer the question as to whether the examined annotations can be regarded as a pattern of the registration in a parish register and so as a text type. The author focuses on the structure and characteristics of different entries. The research area defined in such a manner is based on the outlining of structure and the function of the parish registers and their notes.